Karakterisasi Enam Galur Melon Daging Orange (Cucumis melo L.) di PT. Aditya Sentana Agro - Maghfirani, Siti Faizzatul; Tripatmasari, Mustika; Wijaya, Wakhyono (Universitas Trunojoyo Madura, 2024)
Efforts are made to produce superior seeds and pest and disease resistance through variety assembly. Characterization produces information that is used in planning the creation of melon plants as desired. This study aims to determine the characteristics of six strains of orange flesh melon and determine the kinship relationship of six melon strains. This research was conducted in August-November 2024. This study used a non-factorial Randomized Group Design, with 6 treatments (strains 33, 51, 52, 53, 54, and 55) repeated 3 times. Qualitative data were analyzed in the form of descriptions referring to IPGRI descriptor guidelines (2003). Quantitative data were analyzed by ANOVA, if the results of the analysis were significantly different then further tested using DMRT at the 5% level. The character of leaf shape and leaf color in 6 strains is entire and colored Greyis Olive Green 137 A. The character of male and hermaphrodite flower crown color in G33, G51, G52, G54, and G55 is Vivid Yellow 12 A, G53 is Vivid Yellow 9 A. The character of fruit shape of G33, G51, G52, G53, and G54 is elliptical, while G55 is round. The color of the fruit flesh of G51, G53, and G55 is Strong Orange 25 B. The lowest percentage of senescence was observed in G54 (16.7%). G33, G51, G52, and G54 are closely related with a coefficient value of 83%.